Sistem Antrian di Layanan Administrasi Mahasiswa (LAM) dengan Aplikasi Software Simulasi - William Widjaja; Leli Deswindi (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Queuing problems in social life are common events encountered in everyday life. Waiting in front of the booth to get the service and this situation is a common occurrence. Along with the growth of the community's view of the Universitas Bunda Mulia, the queuing problem is an interesting problem for research.Object research of writer is located at Layanan Administrasi Mahasiswa (LAM) Universitas Bunda Mulia. The research objective is determine an effective service system, which should be applied at the Layanan Administrasi Mahasiswa (LAM) Universitas Bunda Mulia, so the services which provide by staff Layanan Administrasi Mahasiswa (LAM) to student can become more leverage. The method is using a computer simulation, the use of computer simulation in the system design solution has an advantage, which can provide low cost and can compare the original system with the new system. Simulation results showed the model 1 can serve student as much as 81 people, and the average service time each student is 5.76 minutes, whereas the model 2 can serve as many as 82 people, and the average service time each is 5.88 minutes, after the simulations are made and based on observation during the writer’s research at Layanan Administrasi Mahasiswa (LAM) Universitas Bunda Mulia, it can be concluded that the suitable model which can be applied at Layanan Administrasi Mahasiswa (LAM) Universitas Bunda Mulia is model 2, because with model 2 student can gain more leverage service from staff at Layanan Administrasi Mahasiswa (LAM) Universitas Bunda Mulia, student will be served in accordance with their arrival time and with model 2 student will more discipline to obtain services.